Advocacy for a citizen‐centric rule of law agenda: How do we bring the rule of law to life?. Issue 1 (13th August 2021) - Merdzanovic, Adis; Nicolaidis, Kalypso
Abstract: How do we best defend the rule of law against its attackers, both within the European Union and outside of it? Often, the rule of law has been perceived as a domain belonging to jurists, lawyers, bureaucrats, or politicians. Yet at its most fundamental, the rule of law needs to be thought of from a citizen's perspective. When enforced, it guarantees freedoms and liberties for citizens and enables us to live peacefully. In this article, we propose a citizen‐centric rule of law agenda based on a deep conviction that it is if and when it becomes a citizen‐based societal principle that its many attackers are best countered. We discuss the challenges and necessities of rule of law promotion and propose an assessment approach called the "living list". We close with a call for citizen‐scholars to fight for the rule of law, the most precious human invention of all time.